Evaluation of social impact assessment (SIA) practices using SWOT analysis: a case study in India - Ahmad Khairi, Ameera Nazeerah; Ponrahono, Zakiah; Sahrir, Syazwani (Malaysian Institute of Planners, 2022)
Social Impact Assessment (SIA) has been incorporated into part of EIA legislative structures in most nations following the adoption of the National Environmental Policy Act (NEPA) in the USA. The assessment acts as a policy instrument for evaluating a project’s socio-cultural consequences and for advising socio-political stakeholders on its social viability. The instrument also provides operational advice for tackling any negative social effects the policy could have, with a focus on improving its positive effects. However, the traditional SIA has been deemed insufficient for measuring social consequences and has received little emphasis in the appraisal process compared to economic and environmental impacts. Two case studies and a SWOT analysis were conducted to analyse and compare the Social Impact Assessment (SIA) by using a matrix analysis. The findings indicate that both case studies have similar indicators to each term that integrates with one another. The focus on the term is weaknesses, particularly during the redevelopment of a report, which is still lacking in many ways.